Challenges and coping strategies of student mothers of ‘ucc’ college of distance education: The case of the Cape Coast centre: Challenges and coping strategies of student mothers of ‘ucc’ college of distance education: The case of the Cape Coast centre (Journal of Educational Management, 2021)
Student mothers in distance education programmes in Ghana have to combine family roles with work and academic pursuits. Therefore, this study sought to find out the challenges and coping strategies of student mothers at the College of Distance Education (CoDE) of the University of Cape Coast (UCC), Cape Coast Centre. In this descriptive survey, a questionnaire was used to collect data from 175 conveniently sampled student mothers attending classes at Cape Coast Centre, CoDE, UCC. The data collected was analysed using frequencies, percentages, means and standard deviations. The findings from the data gleaned that majority of student mothers (a minimum of 71%) performed a lot of laborious non-academic activities daily in their homes and the combination of these roles with their academics pose a negative high effect on their family lives and academics. Unfortunately, the coping strategies they employed were, to a large extent, ineffective. Thus, student mothers have inevitable academic impediments that emanate from the non-academic activities they perform at home, posing challenges to their academic pursuit. Therefore, CoDE, in collaboration with the Counselling Unit of the University of Cape Coast should provide counselling services to these student mothers to be aware of the academic challenges and ways to effectively navigate these challenges to be successful.
Keywords: student mothers; challenges; coping strategies; distance education